Ethical marketing in India: Exploring the Ethics and Principles of Marketing in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ethical marketing, as the name implies, is a sort of marketing in which businesses attempt tosell their goods and services by not just focusing on the product and its advantages, but alsoconsidering how society would gain from the product's or service's entrance into the market. There are anumber of complaints and allegations that marketing is immoral. The most typical criticisms are that itencourages consumerism, makes implausible promises in marketing, and charges unethical prices,among other things. Regardless of these arguments, marketers must concentrate on improving theirethical standards. Ethical Marketing, Principles of Ethical Marketing, Ethical Values in Marketing,Aspects of Ethical Marketing, and other topics were mostly explored in this research. The Evolution ofMarketing Ethics over Time, Ethical Decision Making in Marketing Factors Affecting It, Marketing ethicsa utilitarian perspective Issues in Marketing Ethics, Ethics in Marketing What It Is and What It Isn't, andEthics Compliance Programs